Preparation method and process of Ti3C2 / TiO2 in-situ composite catalyst for efficient degradation of amoxicillin

The Ti3C2/TiO2 composite catalyst prepared by green in situ oxidation method efficiently degrades amoxicillin residues in the water environment under ultraviolet light, solving the problems of low efficiency and environmental pollution in traditional methods, and achieving efficient and environmentally friendly degradation effects.

CN119588389APending Publication Date: 2025-03-11INNER MONGOLIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411895337.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-21
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is inefficient in removing amoxicillin (AMOX) residues in a water environment, and traditional oxidation methods consume high energy and may produce harmful by-products, resulting in environmental pollution.

Method used

TiO2 was grown in situ with Ti3C2 as the precursor in situ, and Ti3C2/TiO2 composite catalyst was prepared to efficiently degrade AMOX under ultraviolet light.

Benefits of technology

The 90.8% degradation of 30 mg/L AMOX solution was achieved, which was 44.9% higher than that of single-phase Ti3C2 degradation efficiency, and the catalyst has excellent cycle stability and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation method and process of a Ti3C2 / TiO2 in-situ composite catalyst for efficient degradation of amoxicillin, the preparation process of the catalyst is green and environment-friendly, the amoxicillin degradation performance is excellent under ultraviolet light, the degradation rate of 30 mg / L of amoxicillin within 180 min can reach 90.8%, the catalyst is effective in the concentration range of 20-50 mg / L of amoxicillin, the optimal dosage is 0.50 g / L, and the catalyst is suitable for industrial production. After five cycles, high degradation efficiency is still maintained, the cycle stability is good, the large-scale industrial preparation and application potential is achieved, and the harm of drug residues to the environment can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for degrading amoxicillin, a harmful residual organic pollutant, in a water environment, and in particular to a preparation process for a composite catalyst which uses Ti3C2 as a precursor and is in-situ oxidized to TiO2. The catalyst is highly efficient in removing AMOX pollutant residues under ultraviolet light. Background Art

[0002] In recent years, the consumption of medicines has continued to increase and the discharge into the environment has led to the presence of drug residues in the environment as pseudo-persistent substances. Due to the harm caused by drug residues to ecosystems and human life, they have recently been regarded as emerging pollution and have attracted much attention. Among these drugs, antibiotics account for the largest part of medical drugs. The annual consumption of antibiotic drugs for the prevention and treatment of animal and human diseases is between 100,000 and 200,000 tons. Among them, β-lactam antibiotics account for 65% of the entire antibiotic market. The most common β-lactam antibiotic is amoxicillin (AMOX), which is widely used in the treatment of human and veterinary diseases. AMOX has low metabolic activity in the human body (excretion rate is 86%) and is continuously consumed in large quantities, so the detection concentrations in surface water, drinking water and sewage range from nanograms / liter to micrograms / liter. Although the concentration of AMOX in water is relatively low and the toxicity is also low, the rapid growth of drug-resistant pathogens has raised concerns about AMOX residues. Therefore, these residues must be effectively decomposed to reduce their potential risks to the environment and public health.

[0003] Conventional biodegradation is inefficient in removing these pollutants, and many strategies have been proposed in the past few years to address this issue. Among them, photocatalysis is an economical, effective and environmentally friendly method that shows wide applicability in pollutant removal. Titanium dioxide (TiO2) has strong oxidizing properties, non-toxicity and superior chemical stability. As a promising environmentally friendly material, it plays a prominent role in various photocatalytic or photoelectrocatalytic processes ranging from artificial photosynthesis to water purification and water separation. However, the improvement of the photocatalytic performance of TiO2 is severely hindered by its poor light absorption ability and rapid recombination of photogenerated electrons and holes, which greatly inhibits its practical application in water treatment processes. MXenes are a new family of two-dimensional (2D) transition metal carbides or carbonitrides that have attracted increasing attention since their discovery in 2011. The chemical formula of MXenes is M n+1 X n, which is usually obtained by selectively etching the "A" layer in the MAX phase, where X represents C / N elements, A is a IIIA / IVA group element, and M represents an early transition metal. Among various MXenes, Ti3C2 is the most typical one. Ti3C2MXenes materials have been widely studied in the field of photocatalysis due to their superb electronic conductivity, excellent physical and chemical stability, and abundant catalytic active sites. Ti3C2 contains covalent bonds, ionic bonds, metallic bonds, and a large number of functional groups, which provides a very broad space for modification and application. In addition, Ti3C2 as a raw material can be used to obtain a Ti3C2 / TiO2 heterojunction by in-situ oxidation, and a tight bonding connection can be formed between TiO2 and Ti3C2, which can promote the transfer of photogenerated charge carriers, thereby enhancing its photocatalytic ability. However, most oxidation methods require calcination at high temperatures or treatment in a strong acid environment, which are not only energy-intensive, but also may produce harmful byproducts and cause secondary pollution to the environment. Obviously, these methods are very unfriendly to the environment. Therefore, it is necessary to explore some green and mild preparation methods to reduce the impact on the environment. In this study, the Ti3C2 / TiO2 heterojunction was prepared by a green in-situ oxidation method, using hydrogen peroxide as an oxidant. Compared with traditional strong oxidants, the decomposition products of hydrogen peroxide are mainly water and oxygen, which are more environmentally friendly and less likely to produce secondary pollution, which is in line with the concept of green environmental protection. This method not only reduces the environmental risks during the preparation process, but also maintains the high activity and stability of the material, providing a new way to achieve efficient and environmentally friendly photocatalytic degradation.

[0004] This patented design uses a green synthesis strategy to in situ grow TiO2 nanospheres using Ti3C2 as a titanium source to prepare a Ti3C2 / TiO2 composite catalyst, which shows significant potential in the photocatalytic degradation of antibiotic residues in AMOX and has excellent cyclic stability. Summary of the invention

[0005] The specific steps include: Step 1, preparation of Ti3C2: Weigh 2.0 g of 400 mesh Ti3AlC2 and slowly add it into 20 mL of 40 w% HF solution, stir it at room temperature for 18 h, wash it several times by centrifugation with deionized water and anhydrous ethanol, and dry it in a 60 ℃ vacuum oven for 12 h; then add 20 mL of dimethyl sulfoxide and stir it magnetically for 20 h, centrifuge it and wash it with distilled water, ultrasonicate it for 3 h under argon atmosphere, and then centrifuge it and wash it with water to obtain Ti3C2 flakes.

[0006] Step 2, preparation of Ti3C2 / TiO2: The Ti3C2 and H2O2 prepared in step 1 were stirred evenly and transferred to a high-pressure reactor for a constant-temperature hydrothermal reaction. After the reaction was completed, they were naturally cooled to room temperature, and a yellow product was collected by centrifugation. The product was washed alternately with deionized water and ethanol, and then dried in a vacuum oven to obtain a Ti3C2 / TiO2 catalyst. The samples were labeled as TT-n according to the amount of H2O2 added (when the amount of H2O2 added was 0 mL, 0.2 mL, 0.4 mL, 0.6 mL, and 0.8 mL, they were named TT-0, TT-2, TT-4, TT-6, and TT-8, respectively).

[0007] Step 3: Ti3C2 / TiO2 photocatalytic degradation AMOX performance test: The photocatalytic performance of different catalysts was evaluated by degrading AMOX under UV irradiation, and all photocatalytic experiments were carried out three times. The circulating water flow in the reactor ensured that the photocatalytic reaction was carried out at room temperature. During the entire degradation process, 20 mg of the photocatalyst was weighed and dispersed in 40 mL of 30 mg / L AMOX solution, and then stirred in the dark for 60 min to reach adsorption-desorption equilibrium. Under UV irradiation, a certain amount of sample was taken out every 30 min, filtered with a 0.22 µm filter membrane, and the absorbance of the resulting solution was measured at a wavelength of 370 nm using a UV-visible spectrophotometer. After the degradation was completed, the catalyst was recovered by centrifugation, washed with deionized water and ethanol in turn, and then vacuum dried at 60 °C for 12 h. Finally, the treated catalyst was used in multiple cycle experiments to test its stability.

[0008] In step 1, dimethyl sulfoxide is used as a template to induce the conversion of the multilayer stacking structure in the catalyst into a few-layer lamellar structure; the ultrasonic reaction condition is carried out under argon protective gas, the purpose of which is to prevent oxidation of the catalytic material and promote dispersion, thereby precisely regulating the growth and aggregation process of the material and controlling the size and morphology of the material.

[0009] In step 2, the temperature of the isothermal hydrothermal reaction is 170-190 °C, and the isothermal time is 20-25 h.

[0010] In steps 1 and 2, the vacuum drying temperature is 50-60°C and the time is 5-10 h.

[0011] In step 2, the amount of H2O2 added is 0~0.8 mL.

[0012] The beneficial effects of the present invention are: (1) The present invention uses environmentally friendly and mild H2O2 as an oxidant. The Ti3C2 / TiO2 composite catalyst prepared by a simple hydrothermal method can degrade 30 mg / L AMOX solution by 90.8% under 180 min ultraviolet light irradiation. Compared with the single-phase Ti2C3, the degradation efficiency is improved by 44.9%, making the degradation degree more complete and thorough, which helps to reduce the harm caused by drug residues to the water body and other environments, and is beneficial to the protection of the ecological environment.

[0013] (2) The catalyst of the present invention adopts a simple in-situ oxidation method of Ti3C2 to prepare Ti3C2 / TiO2, and a synergistic effect occurs between Ti3C2 and TiO2, which increases the active sites on the catalyst surface, effectively realizes the separation of photogenerated carriers, and thus effectively improves the catalytic activity of the nanocomposite material.

[0014] (3) The in-situ preparation method of Ti3C2 / TiO2 composite photocatalyst can reduce the preparation cost, reduce the complex preparation process and the need to add multiple expensive raw materials, and improve the economic efficiency of material preparation; moreover, the Ti3C2 / TiO2 prepared by in-situ growth has excellent cyclic stability, which is beneficial to actual wastewater treatment and improves the economic efficiency of its use.

[0015] (4) The high degradation efficiency of the material for AMOX means that in actual application scenarios such as the treatment of wastewater containing such pollutants, a better treatment effect can be achieved in a relatively short period of time, reducing the energy consumption and other costs caused by the treatment time, thus saving economic costs in the overall treatment process.

[0016] (5) The catalyst preparation process of the present invention is simple to operate, has high catalytic activity, does not require complex equipment, and uses low-cost raw materials. The AMOX degradation reaction is simple to operate, has high activity, and has no secondary pollution. It has the potential for large-scale industrial preparation and industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 X-ray powder diffraction spectra of Ti3C2, TiO2 and TT-n, where the main diffraction peaks of TiO2 are located at 24.7°, 37.2°, 47.5°, 53.3° and 54.4°, respectively, corresponding to the anatase TiO2 with JCPDS card number 21-1272; the main diffraction peaks of Ti3C2 are located at 8.6°, 17.9°, 44.8° and 60.8°. With the increase of H2O2 addition, the intensity of the Ti3C2 diffraction peak gradually disappears, accompanied by the enhancement of the anatase TiO2 diffraction peak, which indicates that Ti3C2 is gradually oxidized to anatase TiO2.

[0018] Figure 2The scanning electron microscope images of the prepared samples, (a) is Ti3C2, (b) is TiO2, and (c) is TT-2. The scanning results show that Ti3C2 has an accordion-like layered structure; TiO2 presents a nanosphere structure with a diameter range of 100-200 nm; after the two are combined, the sample presents a close composite morphology of nanospheres and layered structures.

[0019] Figure 3 The UV-visible diffuse reflectance spectra of Ti3C2, TiO2 and a series of composite materials show that TiO2 has high absorption in the UV region and almost no absorption in the visible light region, Ti3C2 has high absorbance in the short wavelength region, and the absorbance gradually decreases with the increase of wavelength; after Ti3C2 and TiO2 are composited, the absorption edge moves toward the long wavelength direction, among which the TT-2 absorption edge red-shifts from 400 nm to 460 nm, and then the band gap of TT-2 is reduced from 3.10 eV of TiO2 to 2.21 eV, indicating that the absorption range of light of the composite material is expanded, and more visible light can be used for catalytic reactions.

[0020] Figure 4 The performance of Ti3C2, TiO2 and a series of composite materials in the degradation of AMOX was tested. The photocatalytic degradation activity of pure Ti3C2 and pure TiO2 in AMOX was slightly lower. The activity of Ti3C2 within 180 min was 45.9%, and that of TiO2 was 64.1% ( Figure 4 a); By evaluating a series of TT-n composite catalysts, it was found that TT-2 had the highest photocatalytic activity, which could degrade 30 mg•L -1 The degradation rate of AMOX reached 90.8% ( Figure 4 b).

[0021] Figure 5 a is the removal efficiency test of different concentrations of AMOX on the synthesized TT-2 sample (due to the wide range of AMOX residues). Under ultraviolet light, 0.50 g • L -1 TT-2 catalyst, at 20, 30, 40, 50 mg • L -1 Different AMOX concentrations were tested and it was clear that the catalyst was -1 The degradation rates were 89.7%, 90.7%, 88.3% and 87.0% respectively. Figure 5 b is to test the dosage of the prepared samples and set the initial concentration of AMOX to 30 mg • L -1 The results show that when the catalyst dosage is 0.50 g • L -1When the dosage was less than or more than 0.50 g • L -1 , the AMOX removal rate will decrease, and the dosage is 1.0 g•L -1 The removal efficiency was 87.4% when the amount of photocatalyst was increased. This phenomenon may be due to the turbidity of the reaction solution caused by the increase in the amount of photocatalyst, which inhibited the absorption of light. Therefore, the optimal amount of photocatalyst was determined to be 0.50 g•L -1 .

[0022] Figure 6 The stability of AMOX was tested by photodegradation cycle experiment for TT-2 (AMOX concentration was 30 mg •L -1 ), after five cycles, the photodegradation efficiency of AMOX by TT-2 photocatalyst is still very high, indicating that the catalyst can be recycled and reused many times and has excellent cyclic stability. DETAILED DESCRIPTION

[0023] The present invention will be further described below in conjunction with specific embodiments. Example 1

[0024] Preparation of Ti3C2: Weigh 2.0 g of 400 mesh Ti3AlC2 and slowly add it into 20 mL of 40 w% HF solution, stir at room temperature for 18 h, wash it several times by centrifugation with deionized water and anhydrous ethanol, and dry it in a 60 ℃ vacuum oven for 12 h; then add 20 mL of dimethyl sulfoxide and stir it magnetically for 20 h, centrifuge it and wash it with distilled water, ultrasonicate it under argon atmosphere for 3 h, then centrifuge it and wash it with water to obtain Ti3C2 flakes.

[0025] Ti3C2 photocatalytic degradation AMOX performance test: Add 20 mg Ti3C2 catalyst and 40 mL 30 mg·L -1 AMOX solution was photocatalytically degraded using ultraviolet light as the light source. The light was turned on after the dark reaction reached the adsorption-desorption equilibrium after 60 minutes. Samples were taken every 30 minutes and centrifuged to obtain the supernatant, and its concentration change was measured using a UV-visible spectrophotometer. The degradation rate of AMOX was 45.9% within 180 minutes. Example 2

[0026] TiO2 photocatalytic degradation AMOX performance test: Add 20 mg of commercial TiO2 catalyst and 40 mL of 30 mg·L -1AMOX solution was photocatalytically degraded using ultraviolet light as the light source. The light was turned on after the dark reaction reached the adsorption-desorption equilibrium after 60 minutes. Samples were taken every 30 minutes and centrifuged to obtain the supernatant, and its concentration change was measured using a UV-visible spectrophotometer. The degradation rate of AMOX was 64.1% within 180 minutes. Example 3

[0027] Preparation of TT-0: Take 0.18 g Ti3C2 and add 15 mL deionized water and stir for 30 min, transfer to a high-pressure reactor and react at 180 °C for 12 h. After the reaction, cool naturally to room temperature, collect the yellow product by centrifugation, wash it alternately with deionized water and ethanol, and dry it in vacuum at 70 °C for 12 h.

[0028] TT-0 photocatalytic degradation AMOX performance test: Add 20 mg of TT-0 catalyst and 40 mL of 30 mg·L -1 AMOX solution was photocatalytically degraded using ultraviolet light as the light source. The light was turned on after the dark reaction reached the adsorption-desorption equilibrium after 60 minutes. Samples were taken every 30 minutes and centrifuged to obtain the supernatant, and its concentration change was measured using a UV-visible spectrophotometer. The degradation rate of AMOX was 88.2% within 180 minutes. Example 4

[0029] Preparation of TT-2: Take 0.18 g Ti3C2 and 0.2 mL H2O2, add 15 mL deionized water and stir for 30 min, transfer to a high-pressure reactor and react at 180 °C for 12 h. After the reaction, cool naturally to room temperature, collect the yellow product by centrifugation, wash it alternately with deionized water and ethanol, and dry it in vacuum at 70 °C for 12 h.

[0030] TT-2 photocatalytic degradation AMOX performance test: Add 20 mg of TT-2 catalyst and 40 mL of 30 mg·L -1 AMOX solution was photocatalytically degraded using ultraviolet light as the light source. The light was turned on after the dark reaction reached the adsorption-desorption equilibrium after 60 minutes. Samples were taken every 30 minutes and centrifuged to obtain the supernatant, and its concentration change was measured using a UV-visible spectrophotometer. The degradation rate of AMOX within 180 minutes was 90.8%. Example 5

[0031] Preparation of TT-4: Take 0.18 g Ti3C2 and 0.4 mL H2O2, add 15 mL deionized water and stir for 30 min, transfer to a high-pressure reactor and react at 180 °C for 12 h. After the reaction, cool naturally to room temperature, collect the yellow product by centrifugation, wash it alternately with deionized water and ethanol, and dry it in vacuum at 70 °C for 12 h.

[0032] TT-4 photocatalytic degradation AMOX performance test: Add 20 mg of TT-4 catalyst and 40 mL of 30 mg·L -1 AMOX solution was photocatalytically degraded using ultraviolet light as the light source. The light was turned on after the dark reaction reached the adsorption-desorption equilibrium after 60 minutes. Samples were taken every 30 minutes and centrifuged to obtain the supernatant, and its concentration change was measured using a UV-visible spectrophotometer. The degradation rate of AMOX was 89.0% within 180 minutes. Example 6

[0033] Preparation of TT-6: Take 0.18 g Ti3C2 and 0.6 mL H2O2, add 15 mL deionized water and stir for 30 min, transfer to a high-pressure reactor and react at 180 °C for 12 h. After the reaction, cool naturally to room temperature, collect the yellow product by centrifugation, wash it alternately with deionized water and ethanol, and dry it in vacuum at 70 °C for 12 h.

[0034] TT-6 photocatalytic degradation AMOX performance test: Add 20 mg of TT-6 catalyst and 40 mL of 30 mg·L -1 AMOX solution was photocatalytically degraded using ultraviolet light as the light source. The light was turned on after the dark reaction reached the adsorption-desorption equilibrium after 60 minutes. Samples were taken every 30 minutes and centrifuged to obtain the supernatant, and its concentration change was measured using a UV-visible spectrophotometer. The degradation rate of AMOX was 86.8% within 180 minutes. Example 7

[0035] Preparation of TT-8: Take 0.18 g Ti3C2 and 0.8 mL H2O2, add 15 mL deionized water and stir for 30 min, transfer to a high-pressure reactor and react at 180 °C for 12 h. After the reaction, cool naturally to room temperature, collect the yellow product by centrifugation, wash it alternately with deionized water and ethanol, and dry it in vacuum at 70 °C for 12 h.

[0036] TT-8 photocatalytic degradation AMOX performance test: Add 20 mg of TT-8 catalyst and 40 mL of 30 mg·L -1 AMOX solution was photocatalytically degraded using ultraviolet light as the light source. The light was turned on after the dark reaction reached the adsorption-desorption equilibrium after 60 minutes. Samples were taken every 30 minutes and centrifuged to obtain the supernatant, and its concentration change was measured using a UV-visible spectrophotometer. The degradation rate of AMOX was 87.6% within 180 minutes.

Claims

1. A method and process for preparing a Ti3C2 / TiO2 in-situ composite catalyst for efficient degradation of amoxicillin, characterized in that: The following steps are involved: Step 1, preparation of Ti3C2: weigh 2.0 g of 400 mesh Ti3AlC2 and slowly add it into 20 mL of 40w% HF solution, stir at room temperature for 18 h, wash several times by centrifugation with deionized water and anhydrous ethanol, dry in a 60 °C vacuum oven for 12 h, then add 20 mL of dimethyl sulfoxide and stir magnetically for 20 h, centrifuge and wash with distilled water, ultrasonicate for 3 h under argon atmosphere, then centrifuge and wash and dry to obtain Ti3C2 flakes; wherein dimethyl sulfoxide is used as a template, and ultrasonication is performed under argon protective gas; Step 2, preparation of Ti3C2 / TiO2: The Ti3C2 and H2O2 prepared in step 1 are stirred evenly, transferred to a high-pressure reactor for a constant-temperature hydrothermal reaction, and naturally cooled to room temperature after the reaction is completed. The yellow product is collected by centrifugation, and washed alternately with deionized water and ethanol. The Ti3C2 / TiO2 catalyst is obtained after vacuum drying. The samples are marked as TT-n according to the amount of H2O2 added, and when the amount of H2O2 added is 0 mL, 0.2 mL, 0.4 mL, 0.6 mL, and 0.8 mL, they are named TT-0, TT-2, TT-4, TT-6, and TT-8, respectively; the temperature of the constant-temperature hydrothermal reaction is 170-190 °C, and the constant temperature time is 20-25 h; the vacuum drying temperature is 50-60 °C, and the time is 5-10 h; the amount of H2O2 added is 0-0.8 mL.

2. The preparation method according to claim 1, characterized in that: As described in step 1, Ti3AlC2 was etched using 20 mL of 40w% HF solution to prepare Ti3C2.

3. The preparation method according to claim 1, characterized in that: As described in step 2, different ratios of Ti3C2 / TiO2 are prepared by in-situ oxidation by controlling the H2O2 concentration.

4. Use of the Ti3C2 / TiO2 composite catalyst prepared in situ by the preparation method according to any one of claims 1 to 3 for degrading amoxicillin in a solution under ultraviolet light.

5. The use according to claim 4, characterized in that: The catalyst degraded 30 mg / L amoxicillin by 90.8% under ultraviolet light irradiation for 180 min.

6. The use according to claim 4, characterized in that: The catalyst is effective in the amoxicillin concentration range of 20-50 mg / L, and the optimal photocatalyst dosage is 0.50 g / L.

7. The Ti3C2 / TiO2 composite material obtained by the preparation method according to any one of claims 1 to 6 is used for the purification of β-lactam antibiotic residues.